Calculation Ability Mathematics : Penerapan Model Project Based Lerning di Kelas IV MIS Assu'udiyah Bungo - Resi Artika Devi; Apdoludin Apdoludin; Zulqoidi R. Habibie (CV. Master Literasi Indonesia, 2025)
The class action improved for fourth-grade students at MIS Assu’udiyah Bungo, which has 29 students. Based on the initial observation, the students' math calculation skills were still low. This was shown through the learning process, which was not meeting the requirements of the Merdeka Curriculum. The average math calculation test results for the first semester were still below the school's set standard, which is 75%. The average score was below the target achievement criteria (KKTP) set by the school. The research method used was PTK (Class Action Research). The research was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. The results obtained from the research include: 1) the implementation of the Project Based Learning model for the material on pictograms and bar charts was categorized as very good. The teacher's assessment of the process increased from 97. 06% in cycle I to 100% in cycle II, an increase of 2. 94%, with a final percentage of 100%. Meanwhile, the student's process increased from 69. 37% in cycle I to 81. 4% in cycle II, an increase of 12. 03%, with a final percentage of 81. 4%. Thus, the results achieved the success indicators of the process, which was 76%. 2) The students' math calculation skills on the material of pictograms and bar charts improved above the KKTP of 75% after the implementation of the Project Based Learning model. The learning outcomes for the students in cycle I were 68. 96%, and in cycle II, they reached 93. 10%. It can be concluded that from the initial observation to cycle II, there was an increase of 61%.